PERILAKU RESPON LEKATAN TARIK DAN GESER ANTARA WRAP FRP (FIBRE REINFORCED POLYMER) DENGAN BETON KONVENSIONAL - Wening Wijaya Danu; Adithya Wilda Nova; Han Ay Lie; Purwanto Purwanto (Jurnal Karya Teknik Sipil, 2016)
Retrofitting structures can be done if a building has undergone a change of function, so that the load plan will be exceeded or because of changes in design criteria. Changes in design rules from SNI 03-1726-2002 to SNI 03-1726-2012, resulting in calculated load in the structure becomes larger. The condition occurs causing the need for investigation of the strengths of existing structures. The forces that need to be taken into account in the structure may be greater than the original design. Retrofitting alternatives that can be provided by giving FRP or Fibre Reinforced Polymer. In the use of FRP as reinforcement structure, issues to consider is about the bond between FRP with concrete. The influence of bond due to tensile and shear force that occurs can affects the destruction of the structure. The study by Tudjono et al. (2015) have shown that the beams reinforced with FRP without surface treatment can affect debonding between FRP to concrete. Therefore this study examines the effect of concrete surface roughness due to tensile and shear. From this study, it was concluded that the concrete that do not surface treatment can allow debonding. Treatment of roughness longitudinal, transverse, diagonal, and the cross type gives the same results as effective as compared to plain type. So that on the application in field, the easy surface treatment is selected.